2005
DOI: 10.1016/j.febslet.2005.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent synchronization of gating of syringomycin E ion channels

Abstract: Antifungal lipodepsipeptide syringomycin E (SRE) forms two major conductive states in lipid bilayers: ''small'' and ''large''. Large SRE channels are cluster of several small ones, demonstrating synchronous opening and closure. To get insight into the mechanism of such synchronization we investigated how transmembrane potential, membrane surface charge, and ionic strength affect the number of small SRE channels synchronously functioning in the cluster. Here, we report that the large SRE channels can be present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…1, are commonly used to describe the kinetics of ion channels [15]. Collective action of such channels has been observed in numerous experiments [38][39][40], but the underlying mechanism by which the membrane proteins communicate is still not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…1, are commonly used to describe the kinetics of ion channels [15]. Collective action of such channels has been observed in numerous experiments [38][39][40], but the underlying mechanism by which the membrane proteins communicate is still not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that both the pore radius of small (elementary) channels included in clusters and their ionic selectivity are the same as those of elementary channels that are not included in clusters . Also, the conductances of the clusters are multiples (and integer values) of the conductance of elementary channels. ,, Studies show that the elementary SRE channel is an asymmetric peptide−lipid pore having a conical shape with the wider trans opening formed from host lipid molecules. , These channels are preferentially anion-permeable, and their conductance and kinetics of opening (or closure) are strongly voltage-dependent. ,,, The membrane conductance induced by SRE at fixed voltage increases with the sixth power of SRE concentration, suggesting that at least six toxin molecules are required for channel formation. ,, With negatively charged membranes bathed in 0.1 M NaCl at pH 6, the application of positive voltage opens the SRE channels. A reversal of the voltage sign leads to the closure of the channels.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that SyrE forms asymmetric peptide-lipid pores of a conical shape with predominant anion selectivity ( Malev et al, 2002 ; Ostroumova et al, 2007a ). The properties of single SyrE pores and lipopeptide induced steady-state transmembrane current depend on the boundary potential of membrane ( Feigin et al, 1996 ; Schagina et al, 1998 ; Dalla Serra et al, 1999 ; Ostroumova et al, 2005 , 2007b , 2008 ; Efimova et al, 2018b ). A previous study showed that a decrease in the membrane dipole potential upon addition of small molecule modifiers leads to a reduction of SyrE-pore conductance and dwell time and an increase in the SyrE-induced steady-state transmembrane current ( Ostroumova et al, 2007b , 2008 ; Efimova et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%